Suppose g(x) = f(x) + k. Identify a value of k that transforms f into g.
![Suppose gx fx k Identify a value of k that transforms f into g class=](https://us-static.z-dn.net/files/dc7/f68c220f27acb7457702f5aed75eccbf.png)
Answer:
[tex]k = 5[/tex]
Step-by-step explanation:
Given
[tex]g(x) = f(x) + k[/tex]
Required
Determine the value of k
First, we need to determine the equation of g(x)
Start by calculating the slope (m)
[tex]m = \frac{y_2 - y_1}{x_2 - x_1}[/tex]
Where x and y are two corresponding values:
[tex](x_1,y_1) = (1,1)[/tex]
[tex](x_2,y_2) = (0,-3)[/tex]
The slope (m) is:
[tex]m = \frac{-3- 1}{0 - 1}[/tex]
[tex]m = \frac{-4}{- 1}[/tex]
[tex]m = 4[/tex]
The equation is calculated using:
[tex]y - y_1 = m(x - x_1)[/tex]
Where
[tex]m = 4[/tex] and [tex](x_1,y_1) = (1,1)[/tex]
[tex]y - 1 = 4(x - 1)[/tex]
[tex]y - 1 = 4x - 4[/tex]
Make y the subject of formula
[tex]y = 4x - 4 + 1[/tex]
[tex]y = 4x - 3[/tex]
So:
[tex]f(x) = 4x - 3[/tex]
Next, we determine the equation of f(x)
Start by calculating the slope (m)
[tex]m = \frac{y_2 - y_1}{x_2 - x_1}[/tex]
Where x and y are two corresponding values:
[tex](x_1,y_1) = (-1,-2)[/tex]
[tex](x_2,y_2) = (0,2)[/tex]
The slope (m) is:
[tex]m = \frac{2- (-2)}{0 - (-1)}[/tex]
[tex]m = \frac{2+2}{0+1}[/tex]
[tex]m = \frac{4}{1}[/tex]
[tex]m = 4[/tex]
The equation is calculated using:
[tex]y - y_1 = m(x - x_1)[/tex]
Where
[tex]m = 4[/tex] and [tex](x_1,y_1) = (-1,-2)[/tex]
[tex]y - (-2) = 4(x - (-1))[/tex]
[tex]y + 2 = 4(x +1)[/tex]
[tex]y + 2 = 4x +4[/tex]
Make y the subject of formula
[tex]y = 4x + 4 - 2[/tex]
[tex]y = 4x + 2[/tex]
So:
[tex]g(x) = 4x + 2[/tex]
Recall that
[tex]g(x) = f(x) + k[/tex]
Make k the subject
[tex]k = g(x) - f(x)[/tex]
Substitute values for g(x) and f(x)
[tex]k = 4x + 2 - (4x - 3)[/tex]
[tex]k = 4x + 2 - 4x + 3[/tex]
[tex]k = 4x - 4x+ 2 + 3[/tex]
[tex]k = 5[/tex]
The transformation that maps f into g is a translation transformation,
involving the addition of k to the value of f(x).
Reasons:
Points on the graph of g(x) are; (0, -3) and (0, 1)
[tex]\mathrm{The \ slope \ of \ the \ graph \ of \ g(x)} =\dfrac{-3 - 1}{0 - 1} = 4[/tex]
The equation of g(x) is; y - (-3) = 4·x, which gives;
y = 4·x - 3
The y-intercept = -3
Points on the graph of f(x) are; (-1 -2) and (0, 2)
[tex]\mathrm{The \ slope \ of \ the \ graph \ of \ f(x)} =\dfrac{-2 - 2}{-1 - 0} = 4[/tex]
The equation of f(x) is; y - (-2) = 4·(x - (-1)), which gives;
y = 4·x + 4 - 2 = 4·x + 2
The y-intercept = 2
The slopes of the graphs of f(x) and g(x) are equal, therefore, f(x) ║ g(x)
The difference or the transformation that takes the y-intercept of f(x) to the
y-intercept of g(x) is; k = y-intercept(g(x)) - y-intercept(f(x)) = -3 - 2 = -5
Therefore, k = -5
Which gives;
g(x) = f(x) - 5
The value of k that transforms f into g is; k = -5
Learn more here:
https://brainly.com/question/23570234
https://brainly.com/question/10049947